2019
DOI: 10.1111/1346-8138.15080
|View full text |Cite
|
Sign up to set email alerts
|

A 7‐year follow‐up study on untreated deep or mixed facial infantile hemangioma in East‐Asian patients: When propranolol was not yet an option

Abstract: Infantile hemangioma (IH) is a type of benign tumor that develops during infancy and spontaneously involutes after 1 year of age. Before the introduction of propranolol in 2008, some patients with IH were instructed to wait for the involution without treatment. This long‐term follow‐up study was conducted to assess the prognosis of East‐Asian children with untreated deep or mixed facial IH. Skin sequelae were assessed by comparing images obtained during the patients’ first and last visits in our clinic. Possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
22
1
1
Order By: Relevance
“…They are characterized by rapid proliferation in the early stage, followed by spontaneous regression 1 . However, several studies reported that more than half of untreated IH were not involuted completely, with residual lesions after regression 2–4 . Although oral propranolol could control the growth of IH and reduce the occurrence of serious complications, more than half of the IH treated with systematic propranolol management still had significant or serious residual lesions after regression, requiring additional treatment 5 .…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by rapid proliferation in the early stage, followed by spontaneous regression 1 . However, several studies reported that more than half of untreated IH were not involuted completely, with residual lesions after regression 2–4 . Although oral propranolol could control the growth of IH and reduce the occurrence of serious complications, more than half of the IH treated with systematic propranolol management still had significant or serious residual lesions after regression, requiring additional treatment 5 .…”
Section: Introductionmentioning
confidence: 99%
“…7,11 Studies have reported that more than half of untreated IH has not completely involution, and there residual Sequelae lesions in IH after involution. 8,9,12 These Sequelae lesions include telangiectasia, skin atrophy, excess skin, scars or fibrofatty tissue. This retrospective study showed that 39.5% of superficial IH in the observation group did not completely involution.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lesions are usually self-limiting, residual lesions may still occur in some cases, such as telangiectasia, residual fibers or fatty tissue, atrophy, discoloration, anatomical deformation, or hair loss. 7,8 These residual lesions are permanent and will not subside spontaneously, representing aesthetic and social problems, so surgery is often required. 9 It is reported that more than half of superficial IH will have permanent Sequelae after involution, and thickness seems to be the main influencing factor.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment may include medications, laser therapy, or surgical excision. Beta-blocker drugs and corticosteroids are possible choices for medical therapy [3]. Surgical excision is considered if a hemangioma hinders function, development, or cosmesis.…”
Section: Discussionmentioning
confidence: 99%